Romvac Company – Noutăți în medicină - Cătălina Staicu (Medicamentul Veterinar, 2023)
There is a presentation of the latest achievements of the Romvac Company, which for almost half a century has been one of the most important representatives in the veterinary medicine industry, with a portfolio of 250 biological products and veterinary medicines. Today's endowment of the Romvac Company is at a competitive level ensuring the best conditions in the profile industry from us, especially for the new productions of immunoglobulins (specific IgY) that ensure the company's success. The latest conditionings obtained from the Imuno range (Imuno Baby calf, Imuno Pig, Eczemtrat, Pursept, etc.) are presented. Last but not least, the "biological offensive" carried out by the Company in bringing some ecological bio-insecticides or bio-fungicides to the Romanian market is mentioned.